The Research Progress of Monoclonal Antibody Labeled with 89Zr - Zhanxiong XIAO; Fei DUAN; Hongyu LI (Journal of Isotopes)
Zirconium-89 (89Zr) is a metallic positron-emitting radionuclide. The relatively long half-life and moderate energy making 89Zr especially suitable for the labeling of large biomolecules such as antibodies for radioimmuno-PET (positron emission tomography) imaging. In recent years，significant progress has been made in the research of 89Zr-labeled monoclonal antibodies (mAbs)，driven by the development of mAb therapies. Currently，some of these mAb drugs have entered clinical phases II and III. In the labeling methods of 89Zr，deferoxamine B (DFO) is the most commonly used chelator and has been applied in clinical research. However，researchers are still continually exploring better ligands. In terms of chelator-mAb conjugation techniques，various forms of DFO derivatives remain the primary focus of research. In this article，89Zr labeling methods，chelator conjugation techniques，and advances in 89Zr-mAbs were reviewed. The challenges，issues，and future trends of 89Zr-mAbs has also been discussed and prospected.